PENGARUH AKTIVITAS ZIARAH KUBUR TERHADAP KETENANGAN JIWA DALAM MENGHAFAL AL-QUR’AN SANTRI TAHFIDZ ASRAMA AL-MUJAHIDIN PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Masnida Masnida; Kholid Asrori; Agung Obianto (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2022)
This study aims to determine and analyze how much influence the pilgrimage to the grave has on peace of mind in memorizing the Qur'an of tahfidz students at Al Mujahidin boarding school Darusslam Blokagung Banyuwangi. This type of research uses a quantitative approach, with a population of 28 students. While the technique of taking the sample using the Non Probability Sampling technique, namely taking samples using Saturated Samples, which is a sampling technique where all members of the population are used as samples. So the number of samples used in this study is 28 people with an error rate of 5%. Researchers collect data by means of observation, distributing questionnaires or questionnaires and documentation. The results of this study indicate that the grave pilgrimage has a significant effect on peace of mind in memorizing the Qur'an of tahfidz students at the Al Mujahidin Islamic Boarding School Darusslam Blokagung Banyuwangi in accordance with the t test analysis which shows that the value of p = 0.000 is smaller (<) 0.05 (t count 8.459 is greater (>) t table 2.056).